REGULATION OF FIBER DEVELOPMENT IN COTTON (GOSSYPIUM HIRSUTUM L.) BY microRNAS (Scientific journal of the Fergana State University, 2026)
Cotton (Gossypium spp.) is one of the most important industrial crops worldwide, with both economic and scientific significance. It is primarily cultivated for its high-quality natural fiber. Currently, more than 50 wild, semi-wild, and cultivated species of the genus Gossypium are known, among which four species (G. hirsutum L., G. barbadense L., G. arboreum L., and G. herbaceum L.) are domesticated. Among them, G. hirsutum L. is the most widespread species, accounting for over 90% of global cotton production. This species is distinguished by its high agrobiological potential, adaptability to various climatic conditions, resistance to diseases, and superior fiber quality. Therefore, it is considered the main target for breeding, genetic modification, and modern biotechnological approaches in cotton improvement. Over the past two decades, advances in molecular biotechnology have enabled in-depth studies of this genus’s genome. In this study, the FRS10 gene in the genome of G. hirsutum L. was investigated using RNA interference (RNAi) technology. Downregulation of FRS10 expression resulted in a phenotype of early and complete germination. Germination occurred 3 days earlier compared to control plants, with a germination rate of 99%. Such results indicate that the FRS10 gene could be effectively utilized in genetic engineering and breeding programs.